Developing graphic digital competence in future vocational education teachers: from theory to practice - Bitemirova, Sholpan; Zholdasbekova, Saule; Konakbayeva, U.; Karataev, G.; Zhanbirshiyev, S.; Turalbayeva, A. (Frontiers in Education, 2026)
ObjectiveIn university-level Information and Communication Technology (ICT) training, a persistent gap remains between students’ declarative proficiency with digital tools and the actual quality of their educational graphics. The aim of the study was to enhance the graphic digital competence of undergraduate students enrolled in vocational teacher education programs in Kazakhstan. A three-component approach was introduced, combining cognitive principles, instrumental practice, and reflective analysis.MethodsA quasi-experimental design was implemented at a single university (n = 86; experimental group = 44; control group = 42) over the course of an academic year (~120 academic hours). Diagnostics included a self-assessment questionnaire (Cronbach’s α = 0.82), performance-based tasks in graphic editors, and expert evaluation of students’ artifacts using an analytic rubric. Statistical analyses followed established procedures: paired t-tests for pre–post comparisons within groups, and independent t-tests for posttest comparisons between groups.ResultsThe EG demonstrated a significant pre–post gain on the integrated GDC index: M₁ = 2.09 (SD = 0.44) → M₂ = 2.32 (SD = 0.51), t (43) = 2.74, p < 0.01; no significant change was observed in the CG (p > 0.05). At posttest, the EG showed higher mean scores than CG (M = 2.32 vs. 2.11); the independent t-test approached significance: t (≈84) = 1.95, p = 0.055. Distributional shifts within the EG indicated an upward trend: the percentage of students at a high graphic digital competence (GDC) level increased from 13.6 to 40.9%, while the low-level share decreased from 34.1 to 9.1%. The most pronounced growth occurred in the instrumental component, though cognitive and reflective aspects also improved steadily.ConclusionA modular blend of micro-theory, targeted practicum activities, and reflective portfolio tasks leads to measurable improvement in the quality of students’ educational graphics. This work contributes to the literature by focusing specifically on the graphic dimension of digital competence and offers replicable materials for integration into ICT-based courses.